L`escrime: « en garde ! Êtes-vous prêts ? Allez ! » - Meyer, V.; Rosnet, E.; Guérin, V.; Hornus-Dragne, D.; Dedieu, P.; Poussel, M. (Science & Sports, 2017)
Aims: To present the various aspects of fencing: recreational, competition, elite practice or health-related fencing practice. To help medical practitioners to better understand the specificities of fencing. News: Fencing is a typical and traditional French sport and also the first provider of Olympic medals in France. Nevertheless, fencing still remains poorly known for a large population even for the medical community that may have to take care of fencers. Fencing is an open-skilled combat sport, in which two fencers fight indirectly through their weapons. Fencing is practised with three different weapons (the foil, the épée and the sabre), each contested with different rules. Fencers must wear specific fencing dress, mask, gloves and plastrons. During an assault, the fencer underwent numerous specific constraints leading to the development of physiological and psychological characteristics. Even if fencing is not particularly dangerous, there are some specific injuries that the medical practitioner should know in order to provide the best medical care. In addition, a growing interest for artistic fencing has emerged during the past decades, representing an alternative to the competitive practice. Similarly, the French Fencing Federation developed health-related fencing programs, especially in the field of breast cancer or for women victims of sexual violence. Regarding the various practices of fencing, this sport can be proposed to a large number of people, in accordance to the rules and to the traditions. Conclusion: Fencing is able to develop specific physiological and psychological characteristics. Beyond the vision of competitive fencing, the adaptations of this sport now allow to extend the benefits of fencing to a large population.